2023
DOI: 10.1001/jama.2023.11970
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Dilated Cardiomyopathy in Individuals of African and European Ancestry

Abstract: ImportanceBlack patients with dilated cardiomyopathy (DCM) have increased familial risk and worse outcomes than White patients, but most DCM genetic data are from White patients.ObjectiveTo compare the rare variant genetic architecture of DCM by genomic ancestry within a diverse population of patients with DCM.DesignCross-sectional study enrolling patients with DCM who self-identified as non-Hispanic Black, Hispanic, or non-Hispanic White from June 7, 2016, to March 15, 2020, at 25 US advanced heart failure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…This restricted approach represents the current clinical standard and is the appropriate place to start, but it does not capture the complete genetic landscape of DCM. In the analysis conducted by Jordan et al, 42% of probands of African ancestry and 35.5% of those of European ancestry did not carry a DCM variant in any of the 36 DCM genes, suggesting that the missing heritability of DCM in these patients may reside elsewhere in the genome, such as in noncoding regions of the curated DCM genes, and/or involve common and rare variants in other genes. Recent genome-wide association studies have indicated that the aggregate effects of common variants in noncoding regions can substantially influence risk of DCM and heart failure in general, and capturing this information in the form of polygenic risk scores may ultimately improve DCM genetic testing .…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…This restricted approach represents the current clinical standard and is the appropriate place to start, but it does not capture the complete genetic landscape of DCM. In the analysis conducted by Jordan et al, 42% of probands of African ancestry and 35.5% of those of European ancestry did not carry a DCM variant in any of the 36 DCM genes, suggesting that the missing heritability of DCM in these patients may reside elsewhere in the genome, such as in noncoding regions of the curated DCM genes, and/or involve common and rare variants in other genes. Recent genome-wide association studies have indicated that the aggregate effects of common variants in noncoding regions can substantially influence risk of DCM and heart failure in general, and capturing this information in the form of polygenic risk scores may ultimately improve DCM genetic testing .…”
mentioning
confidence: 98%
“…In this issue of JAMA , Jordan et al investigate the current approach to DCM genetic testing in a multicenter, cross-sectional study of DCM patients enrolled at 25 US heart failure centers. The authors compare burden and predicted pathogenicity of DCM variants in 36 DCM genes across ancestral groups inferred from common variant genotypes.…”
mentioning
confidence: 99%
See 3 more Smart Citations